2022
DOI: 10.1002/eem2.12266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lithium‐Ion Coordination on Lithium Electrodeposition

Abstract: The lithium dendrite and parasitic reactions are two major challenges for lithium (Li) metal anode—the most promising anode materials for high‐energy‐density batteries. In this work, both the dendrite and parasitic reactions that occurred between the liquid electrolyte and Li‐metal anode could be largely inhibited by regulating the Li+‐solvation structure. The saturated Li+‐solvation species exist in commonly used LiPF6 liquid electrolyte that needs extra energy to desolvation during Li‐electrodeposition. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…As one of the most accessible aspects of battery manufacturing, electrolyte engineering is especially attractive. Relying on knowledge learned from Li–ion battery electrolyte design ( 21 23 ), tuning Zn 2+ cation solvation structure by optimizing electrolyte formulations has become a critical and ubiquitous approach to improving Zn anode reversibility, which is especially effective in the case of aqueous electrolytes due to the ability to alter both interfacial structures and solid electrolyte interphase (SEI) chemistries via solvation structures. The emerging superconcentrated “water-in-salt” electrolytes offer opportunities to stabilize the Zn metal anode with a significant amount of salt anions (e.g., > 7 m Cl − [ 7 , 8 ], 20 m bis(trifluoromethylsulfonyl)imide [TFSI − ] [ 9 ]) to partially replace H 2 O in the Zn 2+ solvation sheath, thus suppressing hydrogen evolution, promoting desired Zn–deposition morphology, and improving CE.…”
mentioning
confidence: 99%
“…As one of the most accessible aspects of battery manufacturing, electrolyte engineering is especially attractive. Relying on knowledge learned from Li–ion battery electrolyte design ( 21 23 ), tuning Zn 2+ cation solvation structure by optimizing electrolyte formulations has become a critical and ubiquitous approach to improving Zn anode reversibility, which is especially effective in the case of aqueous electrolytes due to the ability to alter both interfacial structures and solid electrolyte interphase (SEI) chemistries via solvation structures. The emerging superconcentrated “water-in-salt” electrolytes offer opportunities to stabilize the Zn metal anode with a significant amount of salt anions (e.g., > 7 m Cl − [ 7 , 8 ], 20 m bis(trifluoromethylsulfonyl)imide [TFSI − ] [ 9 ]) to partially replace H 2 O in the Zn 2+ solvation sheath, thus suppressing hydrogen evolution, promoting desired Zn–deposition morphology, and improving CE.…”
mentioning
confidence: 99%
“…In 2005, a cubic water box containing 216 molecules was simulated using DC-based and HF-type SE methods . The DFTB method was applied along with the DC method in the 2000s to analyze the structure, mechanics, and dynamics of protein, amylose chain, and bulk water systems. In the last several years, more than 30 computational studies have been reported by utilizing the DCDFTBMD (or its predecessor) program introduced in section . , ,,, ,, ,,,, …”
Section: Illustrative Applicationsmentioning
confidence: 99%
“…Theoretical analyses of the structural, mechanical, and dynamical properties have been performed for various battery electrolytes. ,,,,,, The obstacles for the applications were the lack of DFTB parameters for lithium, one of the essential elements of the carrier cation, and the limited accuracy of existing parameters for some anion species. The parametrization issues were addressed by extending and improving the existing parameter set. ,, The insights obtained from large-scale electrolyte systems containing thousands of atoms have assisted the understanding of experimental measurements. ,, The DC-based DFTB-MD simulation is a promising tool for the theoretical design of new electrolytes.…”
Section: Illustrative Applicationsmentioning
confidence: 99%
“…However, the traditional graphite anode-based LIBs have limited energy density that cannot meet the increasing market demands for a longer cycle life . Compared with the conventional graphite anode, lithium (Li) metal is regarded as the most promising anode material for next-generation rechargeable batteries owing to its high theoretical capacity (3860 mA h/g) and low chemical potential (−3.04 V vs standard hydrogen electrode). , However, lithium metal batteries (LMBs) suffer from undesirable SEI layer formation, uncontrollable Li dendrite growth, and large volumetric changes of Li metal during the Li stripping and Li plating processes. The Li dendrite growth will expose its high surface area to the electrolyte, which accelerates the consumption of the electrolyte and leads to low Coulomb efficiency. , The uncontrollable Li dendrite formation issue is closely related to the Li plating process, which is affected by the lithiophilic property of the substrate materials.…”
Section: Introductionmentioning
confidence: 99%
“…8−11 The Li dendrite growth will expose its high surface area to the electrolyte, which accelerates the consumption of the electrolyte and leads to low Coulomb efficiency. 12,13 The uncontrollable Li dendrite formation issue is closely related to the Li plating process, which is affected by the lithiophilic property of the substrate materials.…”
Section: ■ Introductionmentioning
confidence: 99%